1996
DOI: 10.1097/00005768-199608000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water run training on the maintenance of aerobic performance

Abstract: The purpose of this study was to examine the effect of a 6-wk deep water running program on the maintenance of cardiorespiratory performance (VO2max, ventilatory threshold, running economy); metabolic measurements of blood glucose, blood lactate, and plasma norepinephrine; and body composition. Sixteen trained male runners (VO2max = 58.6 +/- 3.6 ml.kg-1.min-1) were assigned to one of two groups matched by VO2max, treadmill run (R) or water run (WR). Subjects participated in their respective training programs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 23 publications
5
50
0
1
Order By: Relevance
“…The running kinematics was not changed after the 8 week training program. Our kinematical results refutes the following idea proposed by Wilber et al (1996): "It is possible that hydrostatic resistance encountered during water run exercise …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The running kinematics was not changed after the 8 week training program. Our kinematical results refutes the following idea proposed by Wilber et al (1996): "It is possible that hydrostatic resistance encountered during water run exercise …”
Section: Discussionsupporting
confidence: 90%
“…As expected, the physiologic results collectively indicate that DWR and OLR groups exhibit largely similar responses. The physiological responses to DWR and OLR training in this study are in accordance with those from previous studies (Bushman et al, 1997;Eyestone et al, 1993;Morrow, 1995;Wilber et al, 1996). Bushman and coworkers (1997) reported that trained runners attained the following VO 2peak : 63.4 and 62.2 ml.kg −1 .min −1 before and after 4 weeks of DWR, respectively.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…As such, any intervention that can stimulate a physiological response close to normal training conditions in an injured runner, while not hampering the recovery process, must be seen as positive to an otherwise quite traumatic situation. 16 It has been suggested that deep water exercise [17][18][19] or other non-impact exercise 18 offers sufficient stimulus to preserve prior fitness levels amongst healthy participants. However, no assessment of the impact of such an intervention on running dynamics has been performed.…”
Section: Introductionmentioning
confidence: 99%